Relação entre o senso de coerência e alterações bucais de adolescentes - Carolina Freitas Lage (2013)
This cross-sectional study was conducted in order to investigate the relationship between mothers Sense of Coherence (SOC) and adolescents SOC and oral diseases (caries, visible plaque and gingival bleeding) of adolescents. The sample consisted of 366 adolescents between 13 and 15 years, enrolled in primary schools in Itabira, Minas Gerais and their mothers. Data were collected through questionnaires and clinical examination for diagnosis of dental caries, visible plaque and gingival bleeding after calibration of the examiner (intra-examiner Kappa 0.81, 0.76 and 0.80 and inter-examiner 0.80 0.88 and 0.88.) The mothers answered a questionnaire on socioeconomic aspects and a short version of the SOC scale (SOC-13). This same scale was answered by adolescents. Data analysis was performed using the Statistical Package for Social Science (SPSS), version 21.0, and included frequency distribution and association tests. The association between dental caries and the independent variables (age, gender, frequency of brushing, visible plaque, gingival bleeding, frequency of dental visits, adolescent SOC, SOC maternal and economy class) was verified using the chi- square test, chi-square for linear trend and Fisher's exact test (p <0,05). The same tests were used to assess the association between SOC and SOC adolescent mother and the other variables (age, gender, and social class). In addition, we performed logistic regression and Poisson regression with robust variance. The prevalence of each of the oral abnormalities was: dental caries: 17.2%, 9.6% and gingival bleeding visible plaque 47%. The mean values observed in SOC and SOC adolescent mothers were 49.20 and 45.07, respectively. Statistically significant association was observed between dental caries and frequency of dental visits (p <0.001), SOC adolescents (p <0.001) and maternal SOC (p = 0.002). In adjusted logistic regression model, the presence of visible plaque (OR: 3.92 95% CI 2.07 to 7.41) and less favorable economic class (OR: 3.59 95% CI 1.81 to 7.12) remained associated with dental caries regardless of the other variables (age, frequency of dental visits, SOC adolescent and maternal SOC). Considering the SOC adolescents was statistically significant association with gender (p <0.001), age (p = 0.008) and class (p <0.001) and maternal SOC (p <0.001). The variable associated with SOC mother was the class (p <0.001). Higher values of SOC adolescents remained associated with gender (RP: 0.608, 95% CI: 0.487 to 0.760), more privileged economic classes (PR: 2.11, 95% CI 0.359-0.621) and higher values of maternal SOC (RP: 2.01, 95% CI: 1.505 to 2.705). In turn, the SOC mother remained associated with more privileged economic class (RP: 1.396, 95% CI 0.54 to 0.94) and higher values of SOC adolescents (RP: 2,427. 95% CI: 1.77 to 3 31). Thus, it is concluded that caries experience was not associated with breast Sense of Coherence and adolescents in this sample. However, the SOC maternal and adolescents were associated with each other, suggesting that the SOC adolescents may be representative of your dental health and comparable to his family. Moreover, economic class and the presence of visible plaque constitute factors related to dental caries in adolescents.